2018
DOI: 10.31235/osf.io/qsm4x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Damned if you do, damned if you don't? Experimental evidence on hiring discrimination against parents with differing lengths of family leave

Abstract: This study examines how changes in the traditional division of childcare responsibilities affect mothers’ and fathers’ likelihood of getting a job. Can women overcome motherhood penalties by quickly returning to their jobs after childbirth? Do employers discriminate against fathers who take extended family leave? To answer these questions, I exploit some unique features of the parental leave system and job application process in Germany. The findings from my field experiment show that mothers who take nothing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
2
5
0
1
Order By: Relevance
“…Our research shows that one main hindrance for the fathers who wish to take parental leave is the fear of negative career consequences. In reality, we found that few fathers that ultimately take leave actually experience negative consequences for their careers, which supports findings from previous longitudinal and experimental studies in Germany (Bünning 2016;Hipp 2018). Furthermore, we found that men experienced negative consequences of leave less often than women, which reinforces Acker (1990) claim on the workplaces' ability to produce and reinforce gender-specific social inequalities.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our research shows that one main hindrance for the fathers who wish to take parental leave is the fear of negative career consequences. In reality, we found that few fathers that ultimately take leave actually experience negative consequences for their careers, which supports findings from previous longitudinal and experimental studies in Germany (Bünning 2016;Hipp 2018). Furthermore, we found that men experienced negative consequences of leave less often than women, which reinforces Acker (1990) claim on the workplaces' ability to produce and reinforce gender-specific social inequalities.…”
Section: Discussionsupporting
confidence: 90%
“…This observation also holds for the full sample, i.e., also for those parents who had changed employers since the birth of their youngest child, who were self-employed, or who were not employed at the time of the interview. While these findings may be surprising, the results for fathers are actually in line with other findings from Germany based on longitudinal analyses (Bünning 2016) and experimental work (Hipp 2018).…”
Section: Consequences Of Parental Leave For Fathers' and Mothers' Prosupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, we were not able to explore which constraints exactly prevent women from increasing their labor market activity after family care has stopped. The relevance of different factors could be addressed in further research using a qualitative or experimental research design (for experimental research designs on investigating individual's job opportunities, see for example Hipp, 2018;Weisshaar, 2018). It is possible that former family caregivers 'opt' to work reduced hours or to stay out of work (argument derived from the economic theory of the family) or they are rather 'blocked' out by (potential) employers (arguments derived from labor demand side approaches).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists mothers, but not fathers, are penalized during job recruitments (40). To make matters worse, mothers who spend 3-month in parental leave to re-start their career early are discriminated with significantly lower invited interviews compared to mothers with 12-month parental leave, while men`s parental leave duration had no impact (41) suggesting women are at a disadvantage anyway. Especially in academia where contracts are mostly short-term, and pressure is very high to accomplish many things in short time periods.…”
Section: What About Children?mentioning
confidence: 99%